2023
DOI: 10.1111/cod.14374
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of work‐related skin symptoms and associated factors among tertiary hospital workers exposed to cleaning agents in Southern Africa

Zahida Sonday,
Roslynn Baatjies,
Hussein H Mwanga
et al.

Abstract: Introduction Working with cleaning products is associated with occupational contact dermatitis in health workers (HWs), but information on predictors for these outcomes is limited. Objectives This study investigated the prevalence of work‐related skin symptoms (WRSS) and associated factors in HWs exposed to cleaning agents in two Southern African tertiary hospitals. Methods A cross‐sectional study of 697 HWs used an interviewer‐administered questionnaire and assessed for atopy using Phadiatop. Results HWs' med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Hairdressers, construction workers, and healthcare professionals are particularly vulnerable to developing occupational contact dermatitis. Sonday et al conducted a study involving 697 health workers in two tertiary hospitals in Southern Africa and reported that 12.3% of them exhibited a likelihood of contact dermatitis within the past 12 months (105). Additionally, contact with cosmetics and medical supplies was identified as a common source of contact dermatitis (106)(107)(108).…”
Section: Contact Dermatitismentioning
confidence: 99%
“…Hairdressers, construction workers, and healthcare professionals are particularly vulnerable to developing occupational contact dermatitis. Sonday et al conducted a study involving 697 health workers in two tertiary hospitals in Southern Africa and reported that 12.3% of them exhibited a likelihood of contact dermatitis within the past 12 months (105). Additionally, contact with cosmetics and medical supplies was identified as a common source of contact dermatitis (106)(107)(108).…”
Section: Contact Dermatitismentioning
confidence: 99%